LONG AND SHORT SUPPLY CHAIN COEXISTENCE IN THE AGRICULTURAL FOOD MARKET ON DIFFERENT SCALES: OLIGOPOLIES, LOCAL ECONOMIES AND THE DEGREE OF LIBERALISATION OF THE GLOBAL MARKET - M. Paola Sini (European Scientific Journal, ESJ, 2014)
This paper is intended as an approach to the complex matter of the co-existence of long and short chains. It introduces a stimulus to further study these questions more thoroughly, which current market situations lead us to believe will be an interesting field, and one well worthy of consideration. It proposes analysing the advantages and weaknesses of the long and short chain in various different settings and environments. The ultimate aim is to help identify a better combination in the set-up of outlet methods into the agricultural-food markets. The study performed higlights: The effects of the increasing power of largescale retail distribution, hypotesis of future scenarios and the balancerestoring function of the short chain; SWOT analysis of the short supply chain with reference to MEDCs and LEDCs contexts; Connections between short supply chain, self-centred development and protectionism; The nonantagonistic relationship between long and short chain within the districts. The results of the analysis, showing the various, severe repercussions of the individual market’s action on the whole of the agricultural production economy and consumer well-being, highlight the trade-off, at times dramatic, between the various choices of economic and commercial policy. In thus doing, this work remarks the need for new studies aiming to assess the environments of greater relative convenience, those where there may be an overlay, juxtaposition and opposition of the long and short chain, in order to identify optimal coexistence equilibrium in the various contexts, on a local and, overall, global scale, between the two methods of sale on the agricultural food markets system.